Legal Aid in the Case of Torture of Domestic Assistant (Ika Musriati) Accused of Stealing Mobile Phones in Semarang City: Bantuan Hukum dalam Kasus Penyiksaan Asisten Rumah Tangga (Ika Musriati) yang Dituduh Mencuri Ponsel di Kota Semarang - Maharani Athaya Wijanarko; Tiara Rizki Annesha Fanani; Dyah Puspitasari; Annisa Dewi Novihapsari; Sari Rahmaning Tyas (The Indonesian Journal of International Clinical Legal Education, 2022)
Cases of abuse of domestic assistants (ART) are still rampant in Indonesia. One example of a case of abuse occurred in Ika Musriati, a 20-year-old household member in Semarang City. Ika Musriati received inappropriate treatment from her own employer by being brutally tortured. He was abused by his employer, a husband and wife who lived in a housing complex in West Semarang. Not only was he tortured, he was also forced by his employer to eat 50 chilies and drink boiling water, causing damage to his vocal cords and surgery. As an ART, you should be given the right to a life worthiness from an employer. Unlike Ika Musriati, who was not fed when she was hungry, she was even given stale food without side dishes.